Pregnancy Outcome of Cervical Cerclage for Divergent Reasons in Dhofar Region, Oman - Veena Paliwal; Prabha Sinha; Shabnum Sibtain; Salochina Manjan; Ambia Ahmed; Tasabih Ali; Widad Yosuf (Pakistan Journal of Medicine and Dentistry, 2024)
Background: Cervical insufficiency is one of the causes of preterm birth. The object of the study was to compare maternal and neonatal outcomes with different cerclage indications in Dhofar region, Oman.